ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP DIVIDEND PER SHARE (Studi Pada Indeks LQ 45 di BEI Periode 2015- 2017) - Uly Reke, James Sylvanus (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2020)
ABSTRACTDividend or capital gain is one of the goals of the investor or prospective investor in making an investment. The financial performance contained in the financial ratios is often used by investors as information in making investment decisions. Population in this research that all stocks in the LQ 45 index in ISE and is never out of the LQ 45 index from 2015-2017. Purposive sampling used and result in 48 samples of the study. Multiple regression analyses selected in this study with the help of SPSS version 25 with previous data were examined using the classical assumption.The result showed that the independent variables simultaneously have a significant effect on the dividend per share by the Coefficient of Determination (R2 ) is 85,4%. While the partially variable current ratio has no significant effect on the dividend per share. Debt to equity ratio shown a negative also a significant effect on the dividend per share, while earning per share has a significant impact on dividend per share.Keywords: current ratio, debt to equity ratio, earning per share and dividend per share